Induced mutagenesis in Cicer arietinum by the application of EMS and Gamma rays with special reference to the cytological studies - Umavathi, S.; L. Mullainathan, I. Anittha (Journal of Phytology, 2018)
The present study was conducted to analyze the chemical and physical mutagenesis on Cicer arietinum with special reference to cytological studies. In this regard, CO – 4 variety of chick pea was subjected to different concentration of gamma rays (20, 30, 40, 50 and 60kR) and EMS (10, 20, 30, 40 and 50mM) for inducing mutation. The M1 plants exposed to mutagen produces a clear cut difference from the untreated control. The root mitotic studies reveal a wide range of chromosomal aberrations such as stickiness, laggards, bridges and some other precocious movement. The percentage of abnormal cell increased with dosage in both mutagens; and 50mM EMS showed more chromosomal aberrations when compared to gamma rays.